Recurrence of Sipple syndrome - O.V. Safonova; Yu.O. Markevych; A.M. Urbanovych; M.-Yu.Yu. Markevych; A.S. Safonov (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. Multiple endocrine neoplasia (MEN) 2A is a rare autosomal dominant genetic syndrome that is often misdiagnosed or clinically ignored, resulting in delayed treatment of patients. It is predominantly a hereditary disease with a prevalence of 1 per 40,000 people. In half of the cases, MEN syndrome occurs sporadically and is caused by a new mutation in germ or somatic cells. Aim: to improve diagnosis and differential diagnosis of diseases that occur with hypertension, timely diagnosis and appropriate treatment of patients. Materials and methods. We presented a case of diagnosis, treatment and postoperative observation of a patient with recurrence of Sipple syndrome. Results. A 44-year-old man had main complaint of recurrences of hypertensive crises 9 years after diagnosis and treatment for MEN 2A syndrome. A feature of this clinical case was the differential diagnosis of diseases that occur with hypertension to make the correct diagnosis. Conclusions. Patients with MEN syndrome after surgical treatment require careful monitoring throughout life for timely diagnosis and treatment of disease recurrence. Also, an important aspect is genetic examination of family members for the presence of RET proto-oncogene mutations for the purpose of timely diagnosis and prevention of the development of MEN syndrome.